ChemInform Abstract: Palladium Chloride Catalyzed Photochemical Heck Reaction. Issue 45 (14th October 2013) - Waghmode, Suresh B.; Arbuj, Sudhir S.; Wani, Bina N.; Gopinath, C. S.
Abstract A Pd(II)‐catalyzed photochemical Heck‐reaction of aryl iodides with acrylates, acryl amides, and styrene is presented giving cis‐trans‐mixtures of the Heck‐coupling products.